Communicative Language Ability and HOT or LOT of English National Final Examination Test Items - Anni Marhamah; Muhammad Ikbal (Linguista: Jurnal Ilmiah Bahasa, Sastra, dan Pembelajarannya, 2020)
This article aimed to observe and analyzed English national final examination test items for senior high school. This research identified and determined the variation of the test items’ level of questions, analyzed the number of higher order thinking and lower order thinking of the test items and analyzed the communicative language ability that exist in the tests items. This study was conducted through qualitative research focusing on the content analysis method. The data source used in this study was document of English National Examination including the transcript of the listening tests. The data taken from document of English National Examination were all English test items of UN for SMA 2014. The writer took documents of English UN for SMA including the cassette of its listening section from SMA Negeri 1 Rao, Pasaman Regency West Sumatera. The test items were observed, classified, analyzed, and then the results were interpreted and drew the conclusion. This study was done by analyzing the test items document due to the levels of questions and communicative language ability, after all the types was identified and written down, they were used as the basis to make inferences and draw the conclusion.